PERBANDINGAN KINERJA CAMPURAN HOT ROLLED ASPHALT (HRA) DENGAN BAHAN IKAT ASPAL PEN 60/70 DAN ASPAL RETONA BLEND 55 DENGAN VARIASI DURASI RENDAMAN AIR LAUT - Bayu Aditya Pratama; Miftahul Fauziah, S.T., M.T., Ph.D. (TEKNISIA, 2017)
One aspect that is important in highway design is to protect from water. The damage caused by water on the asphalt, such as hole, peel and cracking. If the influence of water in a highway construction is not controlled, it will decrease the value of durability, consequently it will shortening serviceability of highway. The purpose of this research is to determine the performance of Hot Rolled Asphalt mixture with Pen 60/70 and Retona Blend 55 as binder due to variations of the duration of sea water immersion, with observing to the characteristics of Marshall, Indirect Tensile Strength, Index of Retained Strength and their Permeability. Testing of material specifications in this study refers to the specifications. The sea water immersion time are 0 hours; 48 hours; 96 hours; and 192 hours. HRA with asphalt Retona as binder has a value smaller than asphalt Pen 60/70. HRA with Retona are more impermeable than asphalt Pen60/70. The stability HRS with Retona lost of has a percentage of 18, 09 %, is smaller than the loss with asphalt Pen 60/70 the 20, 12 % on the duration of the immersing time 192 hours. The IRS with asphalt Retona be obtained better results in each the length of immersion the sea water than the asphalt Pen60/70. However, the percentage of the decline in the duration of the end of the immersing of the sea water, which is 192 hours, a mixture of HRA with the connective Retona, with a value of 11, 35 % compared with asphalt Pen 60/70 to come down to just 8, 66 %. While the testing of ITS in the duration of immersing time 192 hours with asphalt Retona has a value of 10, 83 %, larger than asphalt Pen 60/70 to the decline in only 6,45 %.